Copyright Perspectives
XIV, 317 p.
Keywords: This book provides international and domestic perspectives on the law of copyright and is led by a foreword on the future of copyright by Dr Francis Gurry, Director General of WIPO and a chapter on the lessons for copyright policy in classical Roman law, by Justice Arthur Emmett. The body of this collection covers current perspectives in the digital age, from the application of the Berne Convention, to time shifting and intermediary copyright liability, as well as perspectives from developing and developed countries covering laws, user rights, open access, government use of copyright material and the use of the criminal law to proscribe copyright infringement.